2020
DOI: 10.19083/ridu.2020.1197
|View full text |Cite
|
Sign up to set email alerts
|

La conducta prosocial como factor protector de los problemas de adicción al juego en universitarios

Abstract: Esta investigación busca analizar las variables implicadas en la conducta prosocial y la capacidad de esta para actuar como un factor protector frente a los problemas de adicción al juego. Este estudio es de tipo cuantitativo, descriptivo, transversal y correlacional. La muestra se compuso por 258 adultos jóvenes universitarios (59.5% mujeres) con una edad media de 20.95 años (DE= 2.19). Se aplicaron cuestionarios (Brief Resilient Coping Scale, cuestionario de apoyo social, Escala de Prosocialidad y South Oaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
8
0
4
Order By: Relevance
“…Another 10.34% did not find any relationship between problematic video-gaming and prosocial behaviour [ 27 , 37 ]. The relationship between prosocial behaviour and gambling was only analysed once [ 32 ], finding that both correlated negatively, with prosocial behaviour being a protective factor against gambling problems.…”
Section: Resultsmentioning
confidence: 99%
“…Another 10.34% did not find any relationship between problematic video-gaming and prosocial behaviour [ 27 , 37 ]. The relationship between prosocial behaviour and gambling was only analysed once [ 32 ], finding that both correlated negatively, with prosocial behaviour being a protective factor against gambling problems.…”
Section: Resultsmentioning
confidence: 99%
“…También hace referencia a recursos familiares que pueden funcionar como factores protectores ante las adicciones tecnológicas. En este sentido, diversos autores coinciden en concebir la conducta prosocial como factor protector de las conductas de riesgo y de las adicciones en la población adolescente (Carlo, Mestre, McGinley, Tur-Porcar, Samper, et al 2014;Cruz, Olmos, y Gonzalo, 2020;Esparza-Reig, 2020) Del mismo modo que ocurre con otros problemas y enfermedades, las conductas adictivas no son el resultado de una única causa o factor, sino que se originan y se mantienen por la interacción de diversos tipos de factores y contexto en el que surgen. De ahí que el presente estudio se oriente a: caracterizar la relación entre el uso de los videojuegos y los factores protectores de la salud mental en una muestra de adolescentes cubanos.…”
Section: Introductionunclassified
“…These models distinguish two major types of academic goals: learning goals and performance goals. Students with learning goals are interested in acquiring new skills and improving their knowledge, even if they make mistakes; students for whom performance goals predominate require positive assessments of their abilities and seek to avoid negative judgments (Alhadabi & Karpinski, 2020;Carvajal et al, 2017;Esparza-Reig, 2020). For their part, other authors, such as Hayamizu and Weiner (1991), divided performance goals into social reinforcement goals and achievement goals.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding learning goals, a range of both international and national studies (Rubilar, 2020;Ruiz-Gutierrez & Santana-Vega, 2018;Sultana & Wirtz, 1992), point out that some young people choose to study the degree for altruistic reasons: they like to work with people at risk of exclusion, children, families and they carry out notable social work. Other studies on the other hand, have found that the choice of Social Work degree is also determined by achievement or social goals: for low-income students, it represents a means of social mobility, offering an opportunity to pursue higher education studies when their family cannot afford to finance the studies of their choice or because they consider it more accessible or less difficult than other degrees (Cortez-Rojas et al, 2020;Esparza-Reig, 2020;Meneses & Coulon, 2020).…”
Section: Introductionmentioning
confidence: 99%